A new model of the upper mantle structure beneath the western rim of the East European Craton - Dec, M.; Malinowski, M.; Perchuc, E. (Solid Earth, 2014)
We present a new 1-D P wave seismic velocity model (called MP1-SUW) of the upper mantle structure beneath the western rim of the East European Craton (EEC) based on the analysis of the earthquakes recorded at the Suwałki (SUW) seismic station located in NE Poland which belongs to the Polish Seismological Network (PLSN). Motivation for this study arises from the observation of a group of reflected waves after expected P410P at epicentral distances 2300–2800 km from the SUW station. Although the existing global models represent the first-arrival traveltimes, they do not represent the full wavefield with all reflected waves because they do not take into account the structural features occurring regionally such as 300 km discontinuity. We perform P wave traveltime analysis using 1-D and 2-D forward ray-tracing modelling for the distances of up to 3000 km. We analysed 249 natural seismic events from four azimuthal spans with epicentres in the western Mediterranean Sea region (WMSR), the Greece and Turkey region (GTR), the Caucasus region (CR) and the part of the northern Mid-Atlantic Ridge near the Jan Mayen Island (JMR). For all chosen regions, except the JMR group for which 2-D modelling was performed, we estimate a 1-D average velocity model which will characterize the main seismic discontinuities. It appears that a single 1-D model (MP1-SUW model) explains well the observed traveltimes for the analysed groups of events. Differences resulting from the different azimuth range of earthquakes are close to the assumed picking uncertainty. The MP1-SUW model documents the bottom of the asthenospheric low-velocity zone (LVZ) at the depth of 220 km, 335 km discontinuity and the zone with the reduction of P wave velocity atop 410 km discontinuity which is depressed to 440 km depth. The nature of the regionally occurring 300 km boundary is explained here by tracing the ancient subduction regime related to the closure of the Iapetus Ocean, the Rheic Ocean and the Tornquist Sea.